2016
DOI: 10.1007/s10068-016-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antioxidative and antimicrobial activities of immature pear (Pyrus pyrifolia cv. Niitaka) fruits by fermentation with Leuconostoc mesenteroides

Abstract: Immature pear ( cv. Niitaka) fruits were fermented with and, which are commonly used as starters for manufacturing fermented foods. Fermented immature pear fruit extracts (FIPF) by showed significantly higher radical-scavenging activity using DPPH, ABTS, superoxide anion, and hydroxyl radicals and reducing power capacity than unfermented immature pear fruit extracts.-FIPF more effectively inhibited the formation of cholesteryl ester hydroperoxide in copper ion-induced rat blood plasma. In addition, the -FIPF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“… Hashemi et al (2017) showed that fermentation improves the chemical properties such as antioxidant activity as well as antibacterial properties compared with unfermented sweet lemon juice, and the fermented juice could be used as a nondairy functional food product. This was consistent with the results obtained after fermentation of immature pear fruits ( Lee et al, 2016 ). Ayed, Ben Abid & Hamdi (2017) also observed the same result, that is, the antioxidant capacity and antibacterial capacity against the tested microorganism of red grape juice after fermentation with kombucha consortium were enhanced.…”
Section: Introductionsupporting
confidence: 93%
“… Hashemi et al (2017) showed that fermentation improves the chemical properties such as antioxidant activity as well as antibacterial properties compared with unfermented sweet lemon juice, and the fermented juice could be used as a nondairy functional food product. This was consistent with the results obtained after fermentation of immature pear fruits ( Lee et al, 2016 ). Ayed, Ben Abid & Hamdi (2017) also observed the same result, that is, the antioxidant capacity and antibacterial capacity against the tested microorganism of red grape juice after fermentation with kombucha consortium were enhanced.…”
Section: Introductionsupporting
confidence: 93%
“…Nowadays, fermented foods are considered important components of the human diet and are widely consumed worldwide. As the most important microorganism in the food industry and human nutrition as well as its wide application in fermented foods, probiotics show various physiological roles, including the improvement of intestinal microflora balance and immunity, antioxidant, anti‐tumor, and antibacterial (Budryn et al., 2019; Konda et al., 2020; Lee et al., 2016; Zhu et al., 2019, 2020). With the increasing demand for flavoring and sensory quality of food as well as health‐conscious in nutrition, food‐associated microbes, especially probiotics, have recently gained more scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…Te content of chlorogenic acid, cafeic acid, arbutin, phenolic compounds, malaxinic acid, favonoids, and antioxidants, which are major compounds in pears, decreases with maturation [41]. Tus, the antioxidant activity and amount of phenolic compounds in immature pears are signifcantly higher than in mature pears [35]. Immature fruits are removed immediately after fowering through fruit thinning to harvest high-quality mature fruits [38], a process in which only one of the seven or eight clusters of fruit is left intact; the remaining are discarded [42].…”
Section: Introductionmentioning
confidence: 95%
“…Pears can be consumed in the form of beverages, purees, jellies, or jams; however, they are mostly consumed as fresh fruit [34]. Unlike other fruits, such as apples, grapes, and tangerines, pears do not have a unique color and scent; therefore, studies on the chemical substances or biological activities in pears are relatively rare [35]. Based on updated research on the chemical substances present in P. pyrifolia Nakai, the most common oriental pear cultivated in Korea, cafeoyl triterpenes [36], a phenylpropanoid malate derivative [37], and other phenolic compounds, such as favonoids, have been found as major active compounds [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%